Advanced skills and research - Sarli, Leopoldo; Taffurelli, Chiara (Acta Biomedica Atenei Parmensis, 2017)
The health organisation has recently been placing emphasis on the importance of the fundamental rights of the individual, promoting an idea of health seen not only from the biological point of view but also and above all in its psychological, relational and social aspects. [...]